Graffiti and street art – from „the broken windows theory” to auction at Sotheby’s house - Gralińska-Toborek, Agnieszka (Granice tolerancji w sztuce i w wychowaniu, 2020)
Street art is one of the most attractive phenomena in contemporary art today. Interestingly, it is largely derived from the illegal graffiti work, which for a long time was considered vandalism and it was not tolerated by the authorities and a large part of society. The history of graffiti is a great example of shifting the limits of tolerance among the art recipients and inside the phenomenon itself, which initially was an expression of independence and rebellion. In this article I would like to follow this process on several simultaneous levels: social, artistic, institutional and educational, each time showing a change going from a negation to an acceptance and even an affirmation.